Migrating gossypiboma mimicking aspergilloma twenty years after mediastinal surgery. (2018) - Kanj, Amjad; Soubani, Ayman O.; Tabaja, Hussam; El Zein, Said; Fares, Mirna; Kanj, Nadim
Abstract: A gossypiboma refers to a surgical sponge or gauze accidentally retained inside a patient during a procedure. It is more commonly encountered after abdominal surgeries. When seen in the thorax, it is usually located within the pleural cavity. We report a case of a 42-year old woman who was found to have a gossypiboma mimicking a simple aspergilloma twenty years after a left thoracotomy. The surgical gauze identified on a CT-scan of her chest appears to have migrated into her lung airways.